Effects of Nutrient Fertility on Growth and Alkaloidal Content in Mitragyna speciosa (Kratom) - Zhang, Mengzi; Sharma, Abhisheak; León, Francisco; Avery, Bonnie; Kjelgren, Roger; McCurdy, Christopher R.; Pearson, Brian J. (Frontiers in Plant Science, 2020)
Leaves harvested from the Southeast Asian tree Mitragyna speciosa (kratom) have a history of use as a traditional ethnobotanical source of medicine to combat fatigue, improve work productivity, and to reduce opioid-related withdrawal symptoms. Kratom leaves contain an array of alkaloids thought to be responsible for the bioactivity reported by users. Interest in the consumptive effects of kratom has led to its recent popularity and use in North America, Western Europe, and Australia. Although the chemistry and pharmacology of select kratom alkaloids are understood, studies have not examined the influence of production environment on growth and alkaloidal content. To directly address this need, 68 kratom trees were vegetatively propagated from a single mother stock to reduce genetic variability and subjected to four varying fertilizer application rates. Leaves were analyzed for chlorophyll concentration, biomass, and alkaloidal content to understand the physiological response of the plant. While increasing rates of fertilizer promoted greater plant growth, relationships with alkaloidal content within leaves were highly variable. Fertility rate had little influence on the concentration of mitragynine, paynantheine, speciociliatine, mitraphylline, and corynoxine per leaf dry mass. 7-Hydroxymitragynine was below the lower limit of quantification in all the analyzed leaf samples. Low to medium rates of fertilizer, however, maximized concentrations of speciogynine, corynantheidine, and isocorynantheidine per leaf dry mass, suggesting a promotion of nitrogen allocation for secondary metabolism occurred for these select alkaloids. Strong correlations (r2 =0.86) between extracted leaf chlorophyll and rapid, nondestructive chlorophyll evaluation (SPAD) response allowed for development of a reliable linear model that can be used to diagnose nutrient deficiencies and allow for timely adjustment of fertilization programs to more accurately manage kratom cultivation efforts. Results from this study provide a greater understanding of the concentration and synthesis of nine bioactive alkaloids in fresh kratom leaves and provide foundational information for kratom cultivation and production.